Reply to Aydin et al: "To what extent is it right to measure serum vaspin, obestatin, and apelin-36 levels without a protease inhibitor in nonalcoholic fatty liver disease?" - EREN, FATİH; YILMAZ, YUSUF (My University, 2011)
[No abstract available]